A Catalytically Essential Motif in External Loop 5 of the Bacterial Oligosaccharyltransferase PglB - Lizak, Christian (American Society for Biochemistry and Molecular Biology, 2014)
Asparagine-linked glycosylation is a post-translational protein modification that is conserved in all domains of life. The initial transfer of a lipid-linked oligosaccharide (LLO) onto acceptor asparagines is catalyzed by the integral membrane protein oligosaccharyltransferase (OST). The previously reported structure of a single-subunit OST enzyme, the Campylobacter lari protein PglB, revealed a partially disordered external loop (EL5), whose role in catalysis was unclear. We identified a new and functionally important sequence motif in EL5 containing a conserved tyrosine residue (Tyr(293)) whose aromatic side chain is essential for catalysis. A synthetic peptide containing the conserved motif can partially but specifically rescue in vitro activity of mutated PglB lacking Tyr(293). Using site-directed disulfide cross-linking, we show that disengagement of the structurally ordered part of EL5 is an essential step of the glycosylation reaction, probably by allowing sequon binding or glyco-product release. Our findings define two distinct mechanistic roles of EL5 in OST-catalyzed glycosylation. These functions, exerted by the two halves of EL5, are independent, because the loop can be cleaved by specific proteolysis with only slight reduction in activity.